A double-reflector antenna of millimeter range with wide-angle scanning - Naumovich, N.; Muravjev, V.; Yurtsev, O.; Moskaliov, D.; Kizimenko, V.; Baty, C. (Видавництво Національного університету "Львівська політехніка", 2009)
It is described the results of numerical simulation and experimental investigation of a double-reflector antenna. The antenna is made according to a certain scheme and it consists of a parabolic reflector (transreflector) horn feed, flat convergent mirror (twistreflector) and a dielectric radome. The transreflector is a thin parabolic radome which has a system of thin wires applied on it. It reflects the waves of linear polarization. The twistreflector turns the plane of polarization around 90.
Keywords: double-reflector antenna; twistreflector; transreflector; scanning; physical optics method; millimeter range